Tissue distribution and sublethal effects of imidacloprid in the South American grayish baywing (Agelaioides badius) - Poliserpi, Maria Belen (2021)
The neonicotinoids are globally used insecticides, which have been shown to cause negative impacts on birds. The current study aimed to evaluate the distribution of the neonicotinoid imidacloprid (IMI) in the tissues of a songbird and identify related physiological effects. Adults of the grayish baywing (Agelaioides baduis) were administered with a single dose of 35 mg IMI/kg, and the IMI concentration was evaluated in liver, kidney and plasma at 4, 12, 24, and 48 h after dosing. At the same time points, effects on hematological, genetic and enzymatic parameters were assessed. Results showed that IMI was absorbed before 4 h, and eliminated at 48 h, in every tissue, and the highest concentrations were detected in plasma. Baywings showed intoxication signs and reduced mobility within the first 5 min post-dosing. Hematological parameters: red blood cells, packed cell volume, hemoglobin, and their derived indices exhibited a transient elevation 24 h after dosing, which coincided with maximum concentrations of IMI in the tissues. No effects were observed on the genotoxicity parameters evaluated: micronuclei and comet assay. Treated birds exhibited an alteration of cholinesterases activity in the muscle and plasma, and of glutathione-S-transferase (GST) activity in the plasma, brain, liver, and muscle. Based on the results obtained, the combined detection of IMI and inhibition of GST activity in the plasma is suggested as a non-lethal biomarker of IMI exposure in wild birds. As efficient field monitoring depends on the availability of proven biomarkers, the current study provides valuable tools for bird conservation in agroecosystems.